Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Stochastic and deterministic processes jointly govern bacterial community assembly along a heterogeneous mangrove degradation gradient - Fei Li; Xingru Tan; Xianling Qin; Mingwei Liu; Xin Liao; Lianghao Pan (Marine Pollution Bulletin, 2026)

Fabricating highly-dispersed W-O-Si structure via silanols modulation over WOx/SiO2 catalyst enables efficient olefin metathesis - Haoxuan Tan; Jianhao Jiao; Yun Zu; Qiang Li; Yucai Qin; Ye Yang; Kai He; Zhongxing Geng; Lijuan Song (Fuel, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Mechanisms and modeling of rock–ice interface shearing at low temperature: Experimental insights and strength prediction based on surface morphology - Ye Li; Xuanmei Fan; Qing Pan; Wensong Wang; Shaochi Peng; Yuheng Qin; Jie Tan (Cold Regions Science and Technology, 2026)

Concentration-dependent roles of hydrazine in immobilized denitrifying biofilm for industrial wastewater treatment - Chenxi Li; Yunfeng Tan; Shengqiang Ma; Jing Wang; Wenlong Bai; Zhi Li; Shengbin Gao; Quanlin Zhao; Jiangzhou Qin; Zhengfang Ye (Bioresource Technology, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Humidity-resilient room-temperature NO2 sensing enabled by epitaxial single-crystalline Bi2WO6 ultrathin films - Liping Tan; Xuefeng Hu; Zilong Wang; Along Li; Weiwei Qin; Ming Zhou; Mudan Feng; Shuang Zhao; Xiaoliang Wang; PeiPei Li; Yali Bi; Wei Zhang (Journal of Hazardous Materials, 2026)

Visible-light-driven CuVO/biochar composite activates periodate for efficient diclofenac degradation: Unveiling the electron-shuttling mechanism of p-benzoquinone - Yuxin liu; Wen Tan; Sinuo Gong; Yang Guo; Jingyi Zhu; Honghui Pan; Qin Shi; Shiyong Huang; Ziyin Li; Chuanqi Zhao (Journal of Environmental Chemical Engineering, 2026)

Zero-valent Fe reshapes microbial and viral communities, regulating arsenic bioavailability reduction in composting: Metagenomic and metaproteomic insights - Guangsheng Qin; Xiaolin Lu; Qiqiang Zhang; Yaling Peng; Linghu Zeng; Rongchun Huang; Yanan Luo; Shengfei Yan; Hui Liang; Zhengzhun Tan; Weijun Pan; Shasha Liang; et al. (Journal of Environmental Chemical Engineering, 2026)

Low-loss AgReMo2O8 (Re = Y, Yb) LTCC ceramics designed by Ag+ common-ion effect for dielectric resonator antenna applications - Jian Bao; Jing Guo; Da Tian; Zhen Fang; Zhen-Tao Wang; Yang Liu; Yang Gao; Cai-Hong Zhang; Biao-Bing Jin; Andreu Cabot; Li-Xia Pang; Kar Ban Tan; et al. (Chemical Engineering Journal, 2026)

Carbon source-regulated redistribution of electron and nitrogen fluxes enhances acetonitrile cometabolic denitrification in immobilized biofilms - Chenxi Li; Shengqiang Ma; Yunfeng Tan; Jing Wang; Wenlong Bai; Zhi Li; Shengbin Gao; Quanlin Zhao; Jiangzhou Qin; Zhengfang Ye (Chemical Engineering Journal, 2026)

ERS-mediated metabolic toxicity: The IRE1α/XBP1s pathway as a critical driver of Cr(VI)-Induced disruption in glucose and lipid metabolism - Limin Zhang; Meina Wu; Luxi Tu; Lanhao Liu; Chunyue Wu; Wanwei Li; Yumei Liu; Mengxiao Luan; Xiaolin Han; Fengjiao Tan; Qin Wang; Xiaohong Li (Chemico-Biological Interactions, 2026)

Coupling Coordination and Driving Mechanisms Between New-Type Urbanization and Ecosystem Service Value in the Beibu Gulf Urban Agglomeration - Qianxi Tan; Yijia Zhou; Ting Luo; Xiaoyue Li; Zhenzhen Li; Menglin Qin (International Journal of Environmental Research, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Chlorine dioxide suppresses Aeromonas through thiol oxidation and modulates hepatic redox–immune responses in Aeromonas salmonicida-infected rainbow trout (Oncorhynchus mykiss) - Baorui Cao; Yan Qin; Tianqing Huan; Junran Tan; Enhui Liu; Wei Gu; Gaochao Wang; Kaibo Ge; Yunchao Sun; Datian Li; Peng Fan; Min Liu; et al. (Fish & Shellfish Immunology, 2026)

Hypoxia-induced downregulation of cAMP drives Ganoderic acid biosynthesis and restricts biofilm development in Ganoderma lucidum - Siyi Wang; Li Tian; Faqin Li; Qin Wang; Yanan Tan; Yanda Ning; Xuewei Cao; Yueqian Liu; Jiaolei Shangguan; Huihui Li; Ailiang Jiang; Mingwen Zhao; et al. (Food Research International, 2026)

Multi-batch treatment of swine slaughterhouse wastewater by microalgal–fungal consortium system: Stability and effects on dissolved organic matter - Zhengsheng Shi; Yequan Sheng; Xin Tan; Yu Xin; Xiaolong Wu; Qin Zhang; Yanbin Li (Environmental Research, 2026)

Preparation and physicochemical synergistic CO2 capture mechanism of all-waste coal gangue-based porous geopolymers - Tan Li; Xuyao Qi; Mujun Chen; Dexin Xu; Yaqi Qin (Chemical Engineering Journal, 2026)

Chemical Characteristics, Sources, and Transport Pathways of PM2.5 in a Mid-Altitude Industrial City of the Upper Yellow River Basin - Lin Yi; Juanjuan Qin; Yuanyuan Qin; Yuwei Gao; Jingnan Li; Xiaoying Su; Shuming Zhang; Zhiguo Rao; Jihua Tan; Peng Yi (Water, Air, & Soil Pollution, 2026)

A multifunctional fluorescent sensor for sequential off-on-off visual detection of Zn2+ and glyphosate in food and biological matrices and efficient removal of Zn2+ from aqueous media - Xiao Han; Yao Li; Xinyi Tan; Wenlong Qin; Haiyan Xu; Chuanxiang Chen (Analytica Chimica Acta, 2026)

Metagenomics-guided construction of novel salt-tolerant bacterial-algal symbiosis for synergistic nitrogen removal at low C/N ratio - Binghui Yu; Haorui Li; Xuenan Yan; Lei Qin; Tiejun Li; Wen Zhang; Yingyu Tan; Xingwei Xiang (Algal Research, 2026)

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

A multi-objective critical component group identification method based on the NSGA-II-PSO-KCAD optimization algorithm: A case study of an automated container terminal - Shipeng Wang; Haiyan Wang; Yang Li; Wenjing Wang; Fuyou Tan; Guoqing Xue; Xushi Ma; Yang Han; Qi Qin (Ocean Engineering, 2026)

Citric acid-assisted MnOx/biochar for periodate activation and diclofenac degradation: A non-radical pathway driven by Mn(III) stabilization - Wen Tan; Yuxin liu; Sinuo Gong; Yang Guo; Jingyi Zhu; Honghui Pan; Qin Shi; Ziyin Li; Chuanqi Zhao (Journal of Environmental Management, 2026)

Microcystin-LR disrupts gut metabolic homeostasis through microbiota–metabolite axis remodeling in grass carp - Lixin Ma; Junyuan Tan; Xiaomin Zheng; Zhuojin He; Zhendong Qin; Li Lin; Fei Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

High-performance conductive eutectogel synthesized by carboxymethyl cellulose-enhanced physicochemical dual network for supercapacitors and wearable electronic devices - Yiheng Ruan; Min Peng; Wang Li; Chuanyang Chen; Zuzeng Qin; Tongming Su; Xuan Luo; Xueqiang Tan; Xinling Xie (Carbohydrate Polymers, 2026)

Two Fatty Acids From Host Plant Leaves Are Attractive to Soritia leptatina Adults - Qianwen Ma; Qin Li; Tingting Tan; Yifei Meng; Hongquan Wang; Yiqu Chen; Xiaoqin Tang (Journal of Chemical Ecology, 2026)

Asymmetric Co-O-La coordination achieves biocompatible and selective generation of high-valent cobalt-oxo species for boosting water purification - Qin-Chen Li; Hai-Yan Zhu; Yi-Jun Zhang; Biao Chen; Yong-Sheng Tan; Ya-Meng Dong; Qi-Nian Wang; Wei-Kang Wang; Dong-Hua Xie; Xing Zhang (Journal of Hazardous Materials, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Aerogel-based biofilm-membrane bioreactor and its preliminary economic assessment for efficient organic removal from high-salinity coalbed methane produced water - Xin Yang; Jiawang Qin; Chaoyang Li; Jiale Wang; Zhaoying Li; Yihua Wu; Chunyan Yang; Wenming Chai; Bin Tan; Baicang Liu (Bioresource Technology, 2026)

Novel processing strategies and evaluation models for bioactive compounds in rice bran - Mei Yang; Changding Gao; Yuhan Wang; Man Zhang; Li Wang; Fengling Tan; Ligong Zhai; Jinlong Zhao; Tengfei Qin; Yijun Liu; Baoshi Wang (Trends in Food Science & Technology, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Microcystis aeruginosa-driven acute toxicity compromises immune–metabolic regulation and hepatocyte integrity in grass carp - Lixin Ma; Junyuan Tan; Xiaomin Zheng; Zhuojin He; Zhendong Qin; Li Lin; Fei Shi (Environmental Pollution, 2026)

Research on multi-dimensional decision-making method of plastic waste management - Shujie Zhao; Lile Cai; Quanyin Tan; Jinhui Li; Yufei Qin (Environmental Impact Assessment Review, 2026)

Enabling high-efficiency recovery of HMX/RDX from energetic wastewater with macroporous resin: A practical strategy for achieving resource-carbon dual goals - Shengqiang Ma; Dinghao Liang; Xiaojun Wang; Yunfeng Tan; Yuqian Shi; Jinmao Ma; Jiaqi Lu; Jiangzhou Qin; Quanlin Zhao; Jing Wang; Wenlong Bai; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Insights into the size effect of Fe3O4 in Fe/AC for Hg0 removal and the corresponding mechanism - Jiawen Tan; Yuan Qin; Jiayi Piao; Zhao Li; Fei Wang; Ping Ning; Kai Li; Yixing Ma; Xin Sun (ENGINEERING Environment, 2026)

Multi-omics analysis and preliminary experimental validation of acetyl tributyl citrate (ATBC) promoting bladder cancer progression via the AKR1B1/EMT axis - Jirong Jie; Qiong Wang; Zhifeng Chen; Chenxi Hu; Zhuocheng Lai; Sulun Ke; Yuanchao Zhu; Fei Li; Qin Fan; Wanlong Tan (Environmental Pollution, 2026)

Intestinal Mysm1 alleviates colitis-associated depression through the serotonin-dependent gut-brain axis - Qiaozhen Qin; Huaqiang Ruan; Zhenhua Xu; Yuanshuai Li; Wenhao Wu; Xiaotong Li; Jinyu Shi; Heyang Zhang; Yue Chen; Jinwei Liu; Yuanrong Qiu; Yifei Tan; et al. (Science Bulletin, 2026)

Seismic Noise Attenuation in Imaging Gathers Using a Residual U-Net: Application to Seismic Data from the Xihu Sag - Dewen Qin; Jian Li; Yong Jiang; Wensun Yin; Xiuping Jiang; Jun Tan; Qingquan Li; Jianlei Zhang; Yanjiao Wang (Journal of Ocean University of China, 2026)

Whole-genome and microbial diversity analyses reveal mechanism of GY8 for enhancing cadmium removal rate of duckweed - Mi Zhang; Yu-Ting Liu; Xiang-Qin Li; Zhi-Qun Chen; Yan Lan; Ai-Juan Tan; Gui-Li Yang (International Biodeterioration & Biodegradation, 2026)

A regulatory biomimetic nanoparticle targeting senescent glioma cells for BNCT treatment - Qi Dai; Zhicheng Zhang; Zhiqing Ben; Xiaoyan Sun; Yufan Yang; Yaxin Qin; QiYao Yang; Xiaoyan Bao; Linjie Wu; Ruolin Jiang; Xin Tan; Xufang Ying; et al. (Chemical Engineering Journal, 2026)

Epigenetic geochemical behavior of fluorine and beryllium in lepidolite residue - Huichun Gong; Pingchao Ke; Xiang Tan; Lingxiu Long; Yuanyong Qin; Lingling Xu; Jian Wang; Guangrong Li; Yipeng Zhou (Chemical Geology, 2026)

Differences in mAb Galactosylation Caused by the Leaching of Manganese Ions from Different Bioreactors - Xiaojing Liu; Guohong Qin; Jiaqi Mao; Guozhu Li; Chengying Tan; Shengnan Xu; Pan Wang; Xiaofei Wang; Yunfei Lin; Dan Xu (Pharmaceutical Research, 2026)

Research hotspots and evolutionary trends in microalgae-derived EPA production: A bibliometric review - Qingting Weng; Xiaoai Lin; Longzao Luo; Lang Tan; Qin Liu; Shiping Lu; Guosheng Li; Zhou Zhang (Algal Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Chitosan/β-glucan/cystine multifunctional hydrogel loading retinol liposomes for efficiently treating UV-induced skin damage and aging - Qingle Song; Yuan Wang; Zekai Tan; Hongping Xiang; Qin Liu; Meiting Li; Lanyue Zhang; Peng Shu (Carbohydrate Polymers, 2026)

Transcriptomic insights into TiO2 nanoparticle-assisted enhancement of growth, lipid production, and dark fermentation wastewater treatment in Chlorella sp. DT025 - Xiaolong Wu; Jialu Xu; Bangxiang He; Qin Zhang; Yequan Sheng; Xin Tan; Yanbin Li (Bioresource Technology, 2026)

Bioaccumulation and toxicity of hexafluoropropylene oxide homologs in Manila clams (Ruditapes philippinarum) compared with PFOA: Correlations with molecular backbone length - Hanlin Qin; Qianqian Geng; Yujie Bi; Zhijun Tan; Chengchen Wu; Fengling Li; Mengmeng Guo (Aquatic Toxicology, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Host protein interactome profiling of Akabane virus glycoprotein Gc reveals specific mitochondrial genes regulate viral replication - Han Gao; Menghua Deng; Mengna Deng; Canyuan Li; Dengshuai Zhao; Xiangxiang Tan; Shengfeng Chen; Limei Qin; Keshan Zhang (Veterinary Microbiology, 2026)

Synergistic Fe/Cu bimetal and phosphate co-modification of durian-derived biochar for superior CL-20 adsorption under extreme acidity: A combined experimental and DFT study - Mohe Zhang; Yunfeng Tan; Nengsheng Liu; Jiangzhou Qin; Chenxi Li; Xintao Wang; Shengqiang Ma; Jinxin Liu; Jianwei Song; Quanlin Zhao; Siping Pang; Zhengfang Ye (Journal of Water Process Engineering, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Hofmeister effect-regulated poly(vinyl alcohol) @ cellulose nanofiber hydrogel-based SERS enhancement and sensing application - Changyan Tan; Rui Li; Qin Yang; Lu Xue; Yong Ye; Ji Zhou; Ning Lin (Carbohydrate Polymers, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Integrated probabilistic forecasting framework for long-term reservoir outflow through dynamic coupling of meteorological–hydrological–engineering processes - Jiaying Tan; Bin Xu; Jian Zhu; Ping-an Zhong; Ran Mo; Jiangyuan Li; Yuanheng Dong; Xinman Qin; Jiayi Jiang; Huili Wang; Lingwei Zhu (Journal of Hydrology, 2025)

Tailoring the asymmetric structure of Cu-Co bimetallic catalysts to promote peroxydisulfate activation for pollutant degradation - Li-Ming Sun; Qin-Chen Li; Yong-Sheng Tan; Qi-Nian Wang; Yi-Lin Lu; Yi-Jun Zhang; Dong-Hua Xie; Heng-Heng Guo; Xing Zhang (Journal of Environmental Chemical Engineering, 2025)

Research on the synergistic recovery of iron and electricity production performance in acid mine drainage using fuel cells - Zhaocong Ren; Yue Zhang; Jinyuan Jiang; Lihong Wei; Haoyang Song; Wei Tan; Yajun Li; Dongni Shi; Lei He; Hongke Qin (Journal of Environmental Chemical Engineering, 2025)

Effects of roasting on the quality characteristics, sensory profiles, and volatile flavor compounds of different cuts of Yanbian yellow beef - Bowen Qin; Xiangji Meng; Rufeng Lian; Jinlong Tan; Chunxiang Piao; Juan Wang; Hongmei Li; Changcheng Zhao; Baide Mu; Guanhao Li (International Journal of Gastronomy and Food Science, 2025)

Performance assessment and mechanistic elucidation of cation exchange resin and hypochlorite coupling-driven volatile fatty acid biosynthesis during sludge fermentation - Minjun Zhao; Yuke Xu; Han Yang; Junsheng Tan; Wenzhuo Li; Qin Zhang (Chemical Engineering Journal, 2025)

Effects of Duckweed Species Diversity on Physiological Responses and Removal Efficiency under Cadmium Stress - Qin Cao; Ai-Juan Tan; Yan Lan; Wen-Bo Zou; Gui-Li Yang (Water, Air, & Soil Pollution, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

LBSR-YOLO: Blueberry health monitoring algorithm for WSN scenario application - Zhiwen Song; Wei Li; Wei Tan; Tao Qin; Changsheng Chen; Jing Yang (Computers and Electronics in Agriculture, 2025)

Risk assessment and underlying mechanisms of pydiflumetofen resistance in Alternaria tenuissima and Alternaria alternata - Lifen Luo; Guangda Shao; Xinyue Li; Tan Dai; Jianqiang Miao; Xingxing Lu; Qin Peng; Xili Liu (Pesticide Biochemistry and Physiology, 2025)

Application of synergistic effects from novel immobilized materials and microbial symbiosis in MBRs: A review - Lei Qin; Haorui Li; Xiu Gu; Kuangyuan Zhang; Tianhua Ji; Yuxuan Zhang; Ruizhi Liu; Xuenan Yan; Wen Zhang; Huirong Wang; Yingyu Tan (Journal of Water Process Engineering, 2025)

Simultaneous detection of multispecies foodborne pathogens using multiple phage-functionalized nanozyme - Mengyuan Tan; Xin Li; Lu Gao; Qin Hu; Zhen-quan Yang; Xuechao Xu (Journal of Hazardous Materials, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Spatial disparities in perfluoroalkyl and polyfluoroalkyl substances exposure and immunosuppressive effects on vaccine induced antibody levels in Guangzhou children - Zhimei Mou; Pingting Zhu; Fenfang Deng; Yang Xu; Pengzhe Qin; Rongfei Peng; Juntao Li; Lei Tan (Environmental Pollution, 2025)

Xanthouhumol relieves stress-induced depressive-like behaviors through the Sirt1/NF-κB/NLRP3 pathway - Gangqiang Lin; Yi Zhang; Jing Qin; Yong He; Li Fan; Qing Tan; Peng Xie (Psychopharmacology, 2025)

New lignans from Phyllanthodendron dunnianum - Li Xu; Jian-Bing Tan; Yu-Ting Zheng; Zi-Huan Sang; Si-Yu Qin; Yuan-Tao Huang; Mei-Fang Li; Zhen-Xing Zou (Natural Product Research, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Removal of CL-20 from waste acid using macroporous resin: Stabilization of waste acid and recovery of CL-20 - Shengqiang Ma; Yunfeng Tan; Nengsheng Liu; Chenxi Li; Xintao Wang; Jinmao Ma; Quanlin Zhao; Jinxin Liu; Jianwei Song; Jiangzhou Qin; Zhengfang Ye (Journal of Hazardous Materials, 2025)

Cultivar-dependent variation in metabolomic profiles and sensory characteristics of Zhuyeqing green tea (Camellia sinensis) - Chen Liu; Mengyi Ren; Meiyi Ning; Yihong Liao; Xiao Du; Li Qin; Wei Chen; Xiangyun Liu; Aimin Wu; Dejian Feng; Daiwen Chen; Liqiang Tan; et al. (Food Bioscience, 2025)

Co-exposure to triclosan and polystyrene nanoplastics on neurodevelopmental toxicity and gut microbiota dysbiosis in zebrafish (Danio rerio) - Danting Wang; Junying Lan; Wentong Meng; Junping Liu; Ruixue Zhou; Chunxia Chen; Li Qin; Bin Tan; Chunyan Huang (Environmental Pollution, 2025)

Engineering optimal pore architecture and defect-rich structure in pitch-derived carbon for efficient sodium-ion storage - Sheng Zhou; Lidan Tan; Tengfei Zhu; Hui Zhu; Jianguang Guo; Xuanke Li; Zhijun Dong; Qin Zhang; Ye Cong (Chemical Engineering Journal, 2025)

Logic-gate nanocompiler for oxidative/reductive molecular parallel detection during hepatic ischemia-reperfusion injury - Tao Tang; Fushou Liu; Longshua Qin; Hao Li; Wen-Ping Lin; Yi-Ping Gu; Fangtao Tan; Linfeng Wang; Huan Liu; Mingxi Zhang; Ran Cui (Chemical Engineering Journal, 2025)

Corrigendum to “QpmH esterase from cotton rhizosphere bacteria: A novel approach for degrading quizalofop-p-ethyl herbicide” [J Hazard Mater 491 (2025) 1–12/138037] - Wenjing Huang; Zebao Tan; Qin Xiao; Xiangying Liu; Kailin Liu; Zuren Li; Xuguo Zhou; Lianyang Bai; Kun Luo (Journal of Hazardous Materials, 2025)

QpmH esterase from cotton rhizosphere bacteria: A novel approach for degrading quizalofop-p-ethyl herbicide - Wenjing Huang; Zebao Tan; Qin Xiao; Xiangying Liu; Kailin Liu; Zuren Li; Xuguo Zhou; Lianyang Bai; Kun Luo (Journal of Hazardous Materials, 2025)

Study on the adsorption mechanism of CL-20 in waste acid by silicic acid: adsorption model and DFT calculation - Yunfeng Tan; Shengqiang Ma; Nengsheng Liu; Xintao Wang; Chenxi Li; Jinmao Ma; Kun Wu; Mohe Zhang; Jinxin Liu; Jianwei Song; Jiangzhou Qin; Quanlin Zhao; et al. (Environmental Research, 2025)

Association of urinary pesticide metabolites and iodine with thyroid volume in school-aged children - Fuhai Zhong; Conghui Xu; Fenfang Deng; Juntao Li; Yuehong Wei; Pengzhe Qin; Rongfei Peng; Lei Tan (Environmental Pollution, 2025)

Study on sand column collapse mechanisms through optical frequency domain reflectometry and particle image velocimetry - Dao-Yuan Tan; Ning Ma; Yong-Qin Li; Hong-Hu Zhu; Lei Gao; Du-Min Yan; Wan-Huan Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Fine-scale mapping and spatiotemporal heterogeneity analysis of industrial CO2 emissions using nighttime light remote sensing in mainland China - Zilong Qin; Li Jiang; Moquan Sha; Xiaolei Li; Jianguang Tu; Xicheng Tan; Zongyao Sha (Environment, Development and Sustainability, 2025)

Research on the role of bamboo species in the restoration of heavy metal-contaminated soil - Qin Cao; Guang-Qian Gou; Zhao-Xia Dai; Ai-Juan Tan; Gui-Li Yang (Journal of Environmental Management, 2025)

Insight into in-situ Fenton-like catalysis by iron-rich sludge-derived iron-carbon composites: Molecular oxygen activation driven by electron transfer in Fe-C structure - Zhuowen Li; Liying Liang; Wen Tan; Yan Liu; Honghui Pan; Qin Shi; Chuanqi Zhao; Shiyong Huang; Xixiang Liu (Journal of Environmental Chemical Engineering, 2025)

Halomonas fermentation promoted the biotransformation of active substances from Dictyophora indusiata pileus and the enhancement of antioxidant capacity - Xueying Zheng; Ying He; Lei Ma; Yanting Sun; Jiazi Yu; Zeguo Feng; Censhu Li; Jiaru Jiang; Xiaoni Zhang; Liguo Qin; Dan Tan; Yali Zhang (Food Bioscience, 2025)

Association of organophosphate flame retardants exposure with liver function and the contrasting mediating roles of inflammatory and oxidative stress pathways - Yingyi Dai; Qin Li; Yongxian Li; Si Zhou; Xiaotong Li; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Pollution, 2025)

Astronomically forcing hydrological controls on salinity variations during the late Ordovician-early Silurian in the Upper Yangtze area: Responses to the monsoon climate and HICE - Min Xiong; Lei Chen; Chongjie Liao; Xin Chen; Xiucheng Tan; Jian Cao; Shuaicai Wu; Hexing Qin; Zuyou Zhang; Gaoxiang Wang; Dazhong Li; Jiaxun Lu (Chemical Geology, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

T-2 toxin-induced splenic injury by disrupting the gut microbiota–spleen axis via promoting IL-6/JAK/STAT1 signaling-mediated inflammation and apoptosis and its mitigation by elemental nano-selenium - Meng Liu; Xue-Wu Li; Hua Sun; Yi-Qin Yan; Zhi-Yuan Xia; Alainaa Refaie; Ni-Ya Zhang; Shuai Wang; Chen Tan; Lv-Hui Sun (Archives of Toxicology, 2025)

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Optimizing Nickel-Based catalysts for UOR: The role of W interface in nickel-selective oxidation reaction (NSOR) enhancement - Yu Duan; Fozia Sultana; Xiaofan Zhang; Xiaoqing Yan; Xiangbowen Du; Meijie Shi; Peng Zhang; Xiaojun Qin; Kaicheng Qian; Tongtong Li; Mingwu Tan; Renhong Li (Chemical Engineering Journal, 2025)

Optimized inner ear organoids for efficient hair cell generation and ototoxicity response modeling - Xuanhe Qin; Liping Fu; Chunying Li; Xilin Tan; Xiaolei Yin (Science China Life Sciences, 2025)

Synergistic effect of nutrient starvation and abscisic acid on growth and starch accumulation in duckweed - Qin Cao; Yue-Qi Zhang; Ai-Juan Tan; Zhu Li; Gui-Li Yang (Planta, 2025)

Validation of Interaction Between Sugarcane miR167d and Predicted Target Gene ScPUM1 and Analysis of Their Expression Under Cold Stress: A Novel Mechanism of miR167d - Qiqi Song; Pengjin Zhu; Jiahui Li; Qin Cheng; Qinliang Tan; Quanguang Zhou; Ping Lv; Zemei Nong (Journal of Plant Growth Regulation, 2025)

A new sulphur-containing metabolite from a mangrove endophytic fungus Aspergillus sp. GXNU-MA - Furong Wu; Wenxiu Zhang; Xianglong Bo; Qin Feng; Meijing Tan; Shichao Ju; Zishuo Song; Jun Li; Xishan Huang (Natural Product Research, 2025)

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

Purification efficacy and mechanism of two constructed wetlands on low C/N agricultural surface runoff pollutants and fluoroquinolone antibiotics - Yali Tan; Jiajun Wang; Qin Zhang; Dandan Xu; Jieyue Li; Yanli Ding; Shaoyuan Bai (Journal of Water Process Engineering, 2025)

Disruption of the endoplasmic reticulum-localized fatty acyl-ACP thioesterase IPF1 caused partial male sterility in rice - Wenye Tan; Jingfei Tian; Wenfeng Zhao; Jianxin Wei; Yibo Xu; Shixu Zhou; Zihan Wei; Zejun Shen; Minghang Wu; Lianguang Shang; Rongbai Li; Yongfei Wang; et al. (Plant Molecular Biology, 2025)

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Monitoring investigation on impact of pile-based PV modules on several typical environmental elements in coastal mudflat intertidal zone - Yonghua Tan; Zipeng Qin; Yan Tian; Dui’an Lu; Qingying Zhao; Ming Gong; Xiaoyan Li (Environmental Monitoring and Assessment, 2025)

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Assessment of the impact of urban block morphological factors on carbon emissions introducing the different context of local climate zones - Yuchen Qin; Jian Kang; Haizhu Zhou; Shen Xu; Gaomei Li; Chenqi Li; Wenjun Tan (Sustainable Cities and Society, 2025)

Integrated response surface and machine learning approach: Experimental optimization and DFT analysis for NaN3 removal via NaClO oxidation - Yunfeng Tan; Jiangzhou Qin; Shengquan Chang; Shengqiang Ma; Linan Su; Nengsheng Liu; Quanlin Zhao; Xintao Wang; Chenxi Li; Jinmao Ma; Kun Wu; Zhengfang Ye (Journal of Water Process Engineering, 2025)

Using multi-modal spectroscopy technology and microscopic analysis to explore the regulation of ultra-high pressure heat-assisted treatment on the texture of ready-to-eat shrimp during storage - Na Li; Zhifeng Tan; Ruida Ma; Yafang Song; Rong Liu; Jiaxin Zhao; Ningbo Qin; Yahong Li; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Multi-omics research reveals the genetic characteristics and acid resistance mechanism of Lactobacillus delbrueckii subsp. lactis DB-8 screening from Xizang fermented dairy - Yali Tan; Sidong Qin; Luoxi Sun; Zhixuan Wang; Xiao Li; Lingyan Liu; Hanjian Zhu; Qingyu Wang; Yanjun Cai; Mengxiang Gao (Food Bioscience, 2025)

Total nutritional double emulsion-based supplement enriched with low-molecular-weight oyster peptides: A promising nutritional strategy for alleviating cachexia in chemotherapy-treated Lewis lung cancer mice - Jinzhen Li; Wenhong Cao; Zhongqin Chen; Haisheng Lin; Jialong Gao; Mingtang Tan; Xiaoming Qin; Huina Zheng (Food Bioscience, 2025)

Facile preparation of porous MXene/cellulose nanofiber composite for highly-sensitive flexible piezoresistive sensors in e-skin - Xiaohai Zhang; Yijie Wang; Lei Zhang; Xinru Zhang; Yajie Guo; Bao Hao; Yongqiang Qin; Qiang Li; Lei Fan; Helei Dong; Qiulin Tan (Chemical Engineering Journal, 2025)

Regulation of silanol nests in zeolite to form stable Td-Co(II) species for efficient propane dehydrogenation - Huihui Deng; Baozhen Li; Wenchun Zheng; Qin Sun; Mengjia Zhu; Jun Zuo; Yu Tang; Lizhi Wu; Li Tan (Chemical Engineering Journal, 2025)

Territorial Ecological Restoration with a High-carbon Storage Focus in the Beibu Gulf Urban Agglomeration of China: Insights from Carbon Metabolism Spatial Security Patterns - Menglin Qin; Yuting Liu; Qianxi Tan; Ziming Zhu; Xinyu Wu; Hongbo Jiang; Hang Li; Qianqian Shi (Chinese Geographical Science, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

Nanozyme bionics mitochondrial revitalizer suppresses ferroptosis in nucleus pulposus cells for disc regeneration - Jinghao Qin; Yanqiu Wang; Lu Tan; Yi Yang; Yeqin Fu; Conghui Wu; Hongli Duan; Changqing Li; Hongli Li; Shen Zhou; Yue Zhou; Minghan Liu (Chemical Engineering Journal, 2025)

A β-ketoacyl-CoA synthase encoded by DDP1 controls rice anther dehiscence and pollen fertility by maintaining lipid homeostasis in the tapetum - Yibo Xu; Shixu Zhou; Jingfei Tian; Wenfeng Zhao; Jianxin Wei; Juan He; Wenye Tan; Lianguang Shang; Xinhua He; Rongbai Li; Yongfei Wang; Baoxiang Qin (Theoretical and Applied Genetics, 2025)

Construction of MIL-100(Fe)-DMA material for efficient adsorption of Sr and Cs ions from radioactive wastewater - Guohui Wang; Qixin Zhang; Lailai Qin; Kaixuan Tan; Chunguang Li; Lianshun Li; Tinggui Yang; Xiaojuan Liu (Science of The Total Environment, 2024)

pH-responsive collagen nanocomposite films reinforced by curcumin-loaded Laponite nanoplatelets for dynamic visualization of shrimp freshness - Jiabo Shi; Li Sheng; Meng Chen; Xiaoyi Wu; Xiaojie Li; Yan Qin Tan (Food Hydrocolloids, 2024)

Combined effects of benzene, toluene, xylene, ethylbenzene, and styrene exposure on hearing loss mediated by oxidative stress at realistic low levels - Yan Liu; Zihao Long; Jingjing Qiu; Qingfei Chen; Aichu Yang; Minghui Xiao; Shanfeng Dang; Yanqun Zhu; Qing Liu; Yanrong Lv; Shuangqi Li; Jingyao Qin; et al. (Environmental Pollution, 2024)

Thyroid hormones and oxidative stress moderated the association between urinary phthalate metabolites and cardiovascular risk factors - Rong He; Hua Bi; Jia He; Yangxu Luo; Xiaotong Li; Qin Li; Rende Huang; Lei Tan (Environmental Pollution, 2024)

Unraveling the intrinsic mechanism of recyclable octahedral Fe3S4-triggered peroxydisulfate activation for contaminant degradation: The pivotal role of high-valent iron-oxo species - Jiaqu Tan; Zhuoxun Tian; Fengjie Qin; Qiaojuan Kong; Dongya Li; Fan Yang; Zhen Zhang; Yulong Zhang; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Integrin A5B1-mediated endocytosis of polystyrene nanoplastics: Implications for human lung disease and therapeutic targets - Mingming Han; Ji Liang; Kai Wang; Qin Si; Chenxi Zhu; Yunlong Zhao; Nurzalina Abdul Karim Khan; Anisah Lee Binti Abdullah; Aileen Tan Shau-Hwai; Yi Ming Li; Zihan Zhou; Chunqi Jiang; et al. (Science of The Total Environment, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Impact of COVID-19 on temporal trends and health risks of urinary metal concentrations among residents of Guangzhou, China - Jia Liao; Rende Huang; Xiangyu Jia; Jia He; Qin Li; Xiaotong Li; Jun Yuan; Lei Tan (Environmental Research, 2024)

Steroid-Refractory Myocarditis Induced by Immune Checkpoint Inhibitor Responded to Infliximab: Report of Two Cases and Literature Review - Sihan Tan; Chang Qi; Hao Zeng; Qi Wei; Qin Huang; Xin Pu; Weimin Li; Yalun Li; Panwen Tian (Cardiovascular Toxicology, 2024)

Longitudinal study and predictive modelling of urinary pesticide metabolite concentrations in residents of Guangzhou, China - Xiangyu Jia; Xiaotong Li; Fenfang Deng; Jia He; Qin Li; Chongshan Guo; Jun Yuan; Lei Tan (Chemosphere, 2024)

The shifting pattern of CO2 source sink in a subtropical urbanizing lightly eutrophic lake - Rongjie Yang; Huixing Song; Qiao Qin; Yingying Chen; Di Li; Yuling Qiu; Kezhu Lu; Yike Tan; Qingqing Chen; Xinhao Cao; Shiliang Liu (Science of The Total Environment, 2024)

Retraction notice to “N-rich and O-poor doped carbon prepared via facile ammonium nitrate assisted hydrothermal carbonization for robust supercapacitors” [J Clean. Prod. (2022) 133903] - Xue-Qin Ma; Bo Zhang; Zhi-Xiang Xu; Yi Tan; Bin Li; Yong-Cai Zhang; Guo-Song Ni; Wei-You Zhou; Rafael Luque; Hui-Yan Zhang (Journal of Cleaner Production, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

Rosiglitazone attenuates Acute Kidney Injury from hepatic ischemia–reperfusion in mice by inhibiting arachidonic acid metabolism through the PPAR-γ/NF-κB pathway - Xiaoyan Qin; Zhengli Tan; Qi Li; Shiyi Zhang; Dingheng Hu; Denghui Wang; Liangxu Wang; Baoyong Zhou; Rui Liao; Zhongjun Wu; Yanyao Liu (Inflammation Research, 2024)

Comprehensive study of chiral herbicide flusulfinam uptake, translocation, degradation, and subcellular distribution in rice (Oryza sativa L.) - Shiling Liu; Xiaoli Li; Heng Zhang; Siying Qin; Liying Liang; Ying Liao; Junqi Zhu; Huihua Tan; Feng Zhao (Pesticide Biochemistry and Physiology, 2024)

Efficacy of a new K3-specific bacteriophage for controlling Klebsiella pneumoniae in milk and its potential to disrupt biofilm formation - Pei Li; Yu Zhou; Genglin Guo; Xiayan Qin; Zimeng Hu; Min Li; Zhongming Tan; Yuqing Liu; Xiangan Han; Jiale Ma; Hong Du; Wei Zhang (Food Control, 2024)

Spontaneous Electrochemical Reconstruction of NiNb2O6@C for High-Rate Lithium-Ion Batteries - Lidan Tan; Sheng Zhou; Yi Jin; Hui Zhu; Qin Zhang; Jianguang Guo; Xuanke Li; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Nano molybdenum trioxide-mediated enhancement of soybean yield through improvement of rhizosphere soil molybdenum bioavailability for nitrogen-fixing microbial recruitment - Qibiao Li; Kan Huang; Zhichen Liu; Xiaoming Qin; Yining Liu; Qiling Tan; Chengxiao Hu; Xuecheng Sun (Science of The Total Environment, 2024)

A deep learning approach for hydrofoil optimization of tidal turbines - Changming Li; Bingchen Liang; Peng Yuan; Qin Zhang; Junzhe Tan; Xiancai Si; Yonghui Liu (Ocean Engineering, 2024)

Insights into the combined toxicity and mechanisms of BDE-47 and PFOA in marine blue mussel: An integrated study at the physiochemical and molecular levels - Qianqian Geng; Liang Zou; Mengmeng Guo; Jixing Peng; Fengling Li; Yujie Bi; Shuqi Jiang; Hanlin Qin; Zhijun Tan (Aquatic Toxicology, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Research on density grading of hybrid rice machine-transplanted blanket-seedlings based on multi-source unmanned aerial vehicle data and mechanized transplanting test - Xicheng Wang; Zehua Li; Suiyan Tan; Hongwei Li; Long Qi; Yuwei Wang; Jiongtao Chen; Chuanyi Yang; Jiaying Chen; Yijuan Qin; Xu Ma (Computers and Electronics in Agriculture, 2024)

Integrating metabolomics and network pharmacology to evaluate the effectiveness of traditional medicinal parts of Chinese herbal medicine Cassia agnes Brenan - Qin Liu; Kuanying Tan; Yi Liu; Xiaohan Tang; Weiqiong Li; Jifei He; Yafang Li; Tao Li; Minggao Zi; Hongyan Yang; Yuyi Chai (South African Journal of Botany, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Hybrid multilayer perceptron and convolutional neural network model to predict extreme regional precipitation dominated by the large-scale atmospheric circulation - Qin Jiang; Francesco Cioffi; Weiyue Li; Jinkai Tan; Xiaoduo Pan; Xin Li (Atmospheric Research, 2024)

Anti-fouling coating with ROS-Triggered On-Demand regulation of inflammation to favor tissue healing on vascular devices - Hui Yan; Lietao Wang; Haoshuang Wu; Yongqi An; Yumei Qin; Zhen Xiang; Huining Wan; Yanfei Tan; Li Yang; Fanjun Zhang; Qing Jiang; Rifang Luo; et al. (Chemical Engineering Journal, 2024)

Engineering of local electron properties optimization in single-atom catalysts enabling sustainable photocatalytic conversion of N2 into NH3 - Tianren Liu; Wensheng Zhang; Qingmei Tan; Weilong Lian; Haiting Lin; Jianshen Li; Dongxue Han; Yingying Fan; Dongdong Qin; Li Niu (Chemical Engineering Journal, 2024)

Design, synthesis, and evaluation of 2,2’-bipyridyl derivatives as bifunctional agents against Alzheimer’s disease - Ren-Xian Tan; Wei-Hao Li; Jia-Min Pang; Si-Min Zhong; Xin-Yi Huang; Jun-Ze Deng; Lu-Yi Zhou; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2024)

Investigating the cooling effects of land cover and landscape patterns surrounding rivers: Insights from the subtropical city of Changsha, China - Jie Tan; Wenjun Kuang; De Yu; Weijun Zhou; Xigui Li; Qin Liu; Libo He (Urban Climate, 2024)

Influence of humic acid on the bioaccumulation, elimination, and toxicity of PFOS and TBBPA co-exposure in Mytilus unguiculatus Valenciennes - Qianqian Geng; Liang Zou; Hong Liu; Mengmeng Guo; Fengling Li; Xiangxiang Liu; Hanlin Qin; Xu Wang; Zhijun Tan (Science of The Total Environment, 2024)

Experimental transformation of nontronite to kaolinite: implication for ferrallitization of Fe/Mg-rich clays in compositional stratigraphy on Mars - Xiaorong Qin; Jiacheng Liu; Wei Tan; Hongping He; Joseph Michalski; Yu Sun; Shangying Li; Binlong Ye; Yiping Yang; Yiliang Li (Icarus, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Data-driven visualization of the dynamics of machine learning in materials research - Zhiwei Ye; Jialing Li; Wenjun Wang; Fanzhi Qin; Keteng Li; Hao Tan; Chen Zhang (Journal of Cleaner Production, 2024)

Co-exposure of petrochemical workers to noise and mixture of benzene, toluene, ethylbenzene, xylene, and styrene: Impact on mild renal impairment and interaction - Qingfei Chen; Qifei Deng; Yan Liu; Zihao Long; Shuangqi Li; Qing Liu; Yanrong Lv; Jingyao Qin; Aichu Yang; Yongshun Huang; Zhaoqing Tan; Dongsheng Wang; et al. (Environmental Pollution, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

Association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with oxidative stress and inflammation - Zhuliangzi Lu; Qin Li; Yingyi Dai; Xinhong Pan; Xiaoyan Luo; Rongfei Peng; Chongshan Guo; Lei Tan (Science of The Total Environment, 2024)

A rapid high-resolution multi-sensory urban flood mapping framework via DEM upscaling - Weikai Tan; Nannan Qin; Ying Zhang; Heather McGrath; Maxim Fortin; Jonathan Li (Remote Sensing of Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Effects of zinc oxide nanocomposites on microorganism growth and protection of physicochemical quality during maize storage - Dong-Dong Zhang; Jin-Feng Zhao; Li-Qin Tan; Qiong Wu; Hao-Xin Lv; Yu-Rong Zhang; Min Zhang (International Journal of Food Microbiology, 2024)

A Ni-Fe-V trimetallic phosphorus-selenium composite supported on carbon cloth as freestanding electrocatalyst for oxygen evolution reaction - Yan Qin; Ruiqing Chai; Zhaoyang Tan; Xinran Hou; Jingde Li; Feichao Wu (Fuel, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Inverse kinetic isotope effect of proton and deuteron permeation through pyridinic N-doped graphene - Jingwen Ba; Jinfan Chen; Renjin Xiong; Jingsong Xu; Haibo Li; Xiayan Yan; Cheng Qin; Rui Li; Qifa Pan; Xinxin Tan; Tao Tang; Xin Xiang; et al. (Chemical Engineering Journal, 2024)

Comammox dominate soil nitrification under different N fertilization regimes in semi-arid areas of Northeast China - Xuewan Feng; Meng Wang; Qian Li; Yubo Qin; Bo Sun; Pan Tan; Hang Liu; Cuilan Li; Jinjing Zhang (Applied Soil Ecology, 2024)

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

Dielectric barrier discharge plasma-coupled rare-earth modified Er3+-BiOI catalytic materials for degradation of organic pollutant benzohydroxamic acid in mineral beneficiation waster: Performance, degradation pathway, and its mechanism - Bingyan Dong; Zhendong Li; Peixiang Wang; Yu Duan; Yanwen Tan; Qin Zhang (Journal of Water Process Engineering, 2023)

Valorization of sewage sludge for facile and green wood bio-adhesives production - Zhi-Xiang Xu; Yi Tan; Xue-Qin Ma; Bin Li; Yong-Xing Chen; Bo Zhang; Sameh M. Osman; Jing-Yang Luo; Rafael Luque (Environmental Research, 2023)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Anti-contactin-associated protein-like 2 antibody autoimmune encephalitis with rapidly progressive parkinsonism: a case report and literature review - Xiaohong Qin; Jieying Li; Yuanyuan Luo; Yunsen He; Xiaoqiang Xiao; Arui Tan; Jun Xiao (Acta Neurologica Belgica, 2023)

Association between polycyclic aromatic hydrocarbon exposure and blood lipid levels: the indirect effects of inflammation and oxidative stress - Si Zhou; Xiaotong Li; Yingyi Dai; Chongshan Guo; Rongfei Peng; Pengzhe Qin; Lei Tan (Environmental Science and Pollution Research, 2023)

Metagenomics reveals taxon-specific responses of soil nitrogen cycling under different fertilization regimes in heavy metal contaminated soil - Xinwei Shi; Weilan Tan; Shuting Tang; Qiujie Ling; Chijian Tang; Peiqing Qin; Shiyu Luo; Yinjun Zhao; Fangming Yu; Yi Li (Journal of Environmental Management, 2023)

A novel fungal-algal coupling system for slaughterhouse wastewater treatment and lipid production - Zhengsheng Shi; Xin Tan; Yanbin Li; Yequan Sheng; Qin Zhang; Jialu Xu; Yong Yang (Bioresource Technology, 2023)

Effects of faba beans (Vicia faba L.) on growth performance, textural quality and physiological indices of tilapia (Oreochromis niloticus) - Qingqing Li; Yao Huang; Xingqian Zhang; Zhendong Qin; Cuiyun Zou; Xiaohong Tan; Xi Xie; Shaowen Liang; Li Lin (Aquaculture, 2023)

Metagenomics combined with metabolomics reveals the effect of Enterobacter sp. inoculation on the rhizosphere microenvironment of Bidens pilosa L. in heavy metal contaminated soil - Yi Li; Xinwei Shi; Weilan Tan; Qiujie Ling; Fengmei Pei; Shiyu Luo; Peiqing Qin; Huijian Yuan; Liuan Huang; Fangming Yu (Journal of Hazardous Materials, 2023)

Fungal myosin-1 homologs as key molecular motors at the membrane–cytoskeleton interface - Qin-Rong Tan; Xiang-dong Li (Fungal Biology Reviews, 2023)

4-hydroxylonchocarpin and corylifol A: The potential hepatotoxic components of Psoralea corylifolia L - Linqi Ouyang; Zhiqiang Fan; Yang He; Long Tan; Guoyan Deng; Qin He; Yiran He; Ting Ouyang; Congjie Li; Qin Zhang; Hongyu Liu; Yajie Zuo (Toxicology Letters, 2023)

Nano zero valent iron in the 21st century: A data-driven visualization and analysis of research topics and trends - Keteng Li; Jialing Li; Fanzhi Qin; Haoran Dong; Wenjun Wang; Hanzhuo Luo; Deyu Qin; Chen Zhang; Hao Tan (Journal of Cleaner Production, 2023)

Deep learning for filtering the ground from ALS point clouds: A dataset, evaluations and issues - Nannan Qin; Weikai Tan; Lingfei Ma; Dedong Zhang; Haiyan Guan; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Antimony isotope fractionation and the key controls in the soil profiles of an antimony smelting area - Jie Liao; Decan Tan; Haibo Qin; Qiao Han; Enguang Liu; Jingan Chen; Zengping Ning; Shehong Li (Journal of Hazardous Materials, 2023)

Using Protection Motivation Theory to examine information-seeking behaviors on climate change - Jun Li; Ping Qin; Yifei Quan; Jie-Sheng Tan-Soo (Global Environmental Change, 2023)

Dissecting SEPALLATA3 Splicing Variant Functions During Arabidopsis Vegetative Growth by amiRNA Technology - Yan-Qin Ma; Zuo-Qian Pu; Qi Meng; Xiao-Min Tan; Liu Yang; Kai-Li Zhang; Ye-Ye Ma; Xuan Huang; Zi-Qin Xu (Journal of Plant Growth Regulation, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Genomics and nitrogen metabolic characteristics of a novel heterotrophic nitrifying-aerobic denitrifying bacterium Acinetobacter oleivorans AHP123 - Xiangqun Zhou; Yuanli Wang; Xin Tan; Yequan Sheng; Yanbin Li; Qin Zhang; Jialu Xu; Zhengsheng Shi (Bioresource Technology, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Transcriptome and metabolome analyses reveal novel insights into the seed germination of Michelia chapensis, an endangered species in China - Wuxian Zhou; Yuanyuan Duan; Xiaogang Jiang; Xuhui Tan; Qin Li; Hua Wang; Yajuan Zhang; Meide Zhang (Plant Science, 2023)

Distribution, source, risk and phytoremediation of polycyclic aromatic hydrocarbons (PAHs) in typical urban landscape waters recharged by reclaimed water - Zheng Zhu; Lanxin Li; Yanan Yu; Liqiong Tan; Zhefeng Wang; Siyu Suo; Chuang Liu; Yiming Qin; Xianchun Peng; Haoran Lu; Wenyan Liang (Journal of Environmental Management, 2023)

An all-in-one strategy for municipal solid waste incineration fly ash full resource utilization by heat treatment with added kaolin - Zhijun Song; Xiaowen Zhang; Yujiao Tan; Qin Zeng; Yilong Hua; Xiaoyan Wu; Mi Li; Xudong Liu; Mingliang Luo (Journal of Environmental Management, 2023)

Properties and pelletization of Camellia oleifera shell after anoxic storage - Zhongliang Huang; Hongli Chen; Mengjiao Tan; Liqiang Zhang; Xiaoli Qin; Xuan Zhang; Jinxing Zhou; Renhua Zhong; Hui Li (Biomass and Bioenergy, 2023)

Effects of carbonate minerals and exogenous acids on carbon flux from the chemical weathering of granite and basalt - Chaojun Li; Pete Smith; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Qin Li; Jinfeng Wang; Luhua Wu; Fei Chen; Yuanhong Deng; Zeyin Hu; Yujie Yang; et al. (Global and Planetary Change, 2023)

Moderate-Intensity Treadmill Exercise Promotes mTOR-Dependent Motor Cortical Neurotrophic Factor Expression and Functional Recovery in a Murine Model of Crush Spinal Cord Injury (SCI) - Zuxiong Zhan; Lu Pan; Ying Zhu; Yunhang Wang; Qin Zhao; Yuan Liu; Sen Li; Haiyan Wang; Ce Yang; Lehua Yu; Ying Yin; Botao Tan (Molecular Neurobiology, 2023)

Exosomal miR-767 from senescent endothelial-derived accelerating skin fibroblasts aging via inhibiting TAB1 - Jing Li; Jiyong Tan; Qiong Song; Xinni Yang; Xin Zhang; Hao Qin; Gaoxiang Huang; Xiaoxue Su; Jing Li (Journal of Molecular Histology, 2023)
Skin aging is a complicated physiological process, and microRNA-mediated regulation has been shown to contribute to this process. Exosomes mediate intercellular communication through miRNAs, mRNAs and proteins, and participate in many physiological and pathological processes. Vascular endothelial cell-derived exosomes have been confirmed to be involved in the development of many diseases, however, their effects on skin aging have not been reported. In this study, senescent endothelial cells could regulate skin fibroblast functions and promote cell senescence through exosomal pathway. miR-767 was highly expressed in senescent vascular endothelial cells and their exosomes, and miR-767 is also upregulated in skin fibroblasts after treatment with exosomes derived from senescent vascular endothelial cells. In addition, transfection with miR-767 mimic promoted senescence of skin fibroblasts, while transfection with miR-767 inhibitor reversed the effect of D-galactose. Double luciferase analysis confirmed that TAB1 was a direct target gene of miR-767. Furthermore, miR-767 expression was increased and TAB1 expression was decreased in D-galactose induced aging mice. In mice that overexpressed miR-767, HE staining showed thinning of dermis and senescence appearance. In conclusion, senescent vascular endothelial cell-derived exosome mediated miR-767 regulates skin fibroblasts through the exosome pathway. Our study reveals the role of vascular endothelial cell-derived exosomes in aging in the skin microenvironment and contributes to the discovery of new targets for delaying senescence.

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Stepwise solid phase extraction integrated with chemical derivatization for all-in-one injection LC-MS/MS analysis of metabolome and lipidome - Jie Chen; Pei Zhang; Siyuan Qin; Bei Tan; Siqi Li; Shaoran Tang; Chuyao Liao; Ying Zhang; Zunjian Zhang; Fengguo Xu (Analytica Chimica Acta, 2023)

Galvanic replacement reaction-regulated photoelectric response and enzyme-mimicking property of ionic liquid functionalized Cu@Cu2O aerogels for dual-mode immunoassay - Jinli Li; Hengjia Wang; Mingwang Liu; Ying Qin; Rong Tan; Liuyong Hu; Wenling Gu; Chengzhou Zhu (Chemical Engineering Journal, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

Knockdown of lncRNA-ASLNC12002 alleviates epithelial–mesenchymal transition of type II alveolar epithelial cells in sepsis-induced acute respiratory distress syndrome - Kaixuan Feng; Weifeng Huang; Jiawei Shang; Feng Ping; Qin Tan; Wei Wang; Yingchuan Li; Yongmei Cao (Human Cell, 2022)
Patients with sepsis-induced acute respiratory distress syndrome (ARDS) have higher mortality and poor prognosis than pneumonia-induced ARDS. Pulmonary fibrosis is an irreversible accumulation of connective tissue in the interstitium of the lung and closely associated with the epithelial–mesenchymal transition (EMT) of type II alveolar epithelial cells (AECIIs). Therefore, it is undoubtedly worth studying whether the EMT of AECIIs in sepsis-induced ARDS patients is different from that in patients with pneumonia-induced ARDS in the regulatory mechanism. Here, we will report for the first time that an lncRNA-ASLNC12002 is highly expressed in AECIIs of patients with sepsis-induced pneumonia and promotes EMT in AECIIs. The research results showed that the expression of ASLNC12002 in AECIIs derived from patients with sepsis-induced ARDS is significantly higher than that in normal people and pneumonia-induced ARDS patients. Mechanism research showed that ASLNC12002 can cause the inactivation of the anti-EMT pathway NR2F2/miR128-3p/Snail1 by acting as the sponge of miR128-3p. Functional experiments showed that targeted silencing of ASLNC12002 could effectively inhibit EMT progression in AECIIs of patients with sepsis-induced pneumonia by restoring NR2F2/miR128-3p/Snail1 pathway. In a word, our study shows for the first time that the inactivation of NR2F2/miR128-3p/Snail1 pathway caused by the enhanced expression of ASLNC12002 is the direct reason why AECIIs in sepsis-induced ARDS patients are prone to get EMT progress. ASLNC12002 has the potential to become a biological target for the prevention and treatment of pulmonary fibrosis in patients with sepsis-induced ARDS. At the same time, the expectation that ASLNC12002 and its related products may be used as clinical markers for the evaluation of early pulmonary fibrosis in ARDS patients should not be ignored.

Numerical Simulation of Fully Coupled Flow-Field and Operational Limitation Envelopes of Helicopter-Ship Combinations - Yihua Cao; Yihao Qin; Wenyuan Tan; Guozhi Li (Journal of Marine Science and Engineering, 2022)
Landing a helicopter to the ship flight deck is most demanding even for the most experienced pilots and modeling and simulation of the ship-helicopter dynamic interface is a substantially challenging technical problem. In this paper, a coupling numerical method was developed to simulate the fully coupled ship-helicopter flow-field under complete wind-over-deck conditions. The steady actuator disk model based on the momentum source approach and the resolved blade method based on the moving overset mesh method were employed to model the rotor. Two different ship-helicopter combinations were studied. The helicopter flight mechanics model was established and then the influences of coupled airwake on the helicopter were analyzed. Finally, based on the derived rejection criterion of safe landing and the developed numerical method, the flight envelopes for these two ship-helicopter combinations were predicted. The steady actuator disk model was found to be effective in the study of helicopter operations in the shipboard environment. The calculated flight envelopes indicate that an appropriate wind direction angle is beneficial to increasing the allowable maximum wind speed and the operating boundary is affected by the rotation direction of the main rotor.

Repeated Sevoflurane Exposures in Neonatal Rats Increased the Brain Vulnerability to Future Stress Exposure and Resulted in Fear Extinction Deficit - Ben-zhen Chen; Li-hua Jiang; Ling Tan; Wen-qin Zhou; Yu-chao Shang; Fang Li; Bin Liu (Neurotoxicity Research, 2022)

Localization of salt-tolerant QTL in rice germination stage under different salinity concentrations - Yanning Wang; Liping Chen; Guiting Song; Tao Huang; Guangliang Wu; Jingai Tan; Peng Wang; Qin Cheng; Caijing Li; Qi Zhong; Shiying Huang; Mengmeng Yang; et al. (Euphytica, 2022)

Allelically and Differentially Expressed Genes After Infection of Edwardsiella ictaluri in Channel Catfish as Determined by Bulk Segregant RNA-Seq - Yulin Jin; Tao Zhou; Wansheng Jiang; Ning Li; Xiaoyan Xu; Suxu Tan; Huitong Shi; Yujia Yang; Zihao Yuan; Wenwen Wang; Guyu Qin; Shikai Liu; et al. (Marine Biotechnology, 2022)

Analysis the Characteristic of Energy and Damage of Coal-Rock Composite Structure Under Cycle Loading - Tan Li; Guangbo Chen; Zhongcheng Qin; Qinghai Li (Geotechnical and Geological Engineering, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

Synthesis, characterization, and antioxidant activity of carboxymethyl chitosan derivatives containing sulfonium salt - Xueqi Sun; Jingjing Zhang; Yingqi Mi; Qin Miao; Wenqiang Tan; Qing Li; Zhanyong Guo (Journal of Oceanology and Limnology, 2022)

Numerical simulation study on the influence of crack characteristics on mechanical properties and impact failure of rock - Tan Li; Guangbo Chen; Zhongcheng Qin; Qinghai Li; Yanhui Li (Arabian Journal of Geosciences, 2021)

Additive and Epistatic QTL on Cadmium (Cd) Tolerance Associated with Seed Germinating Ability in Rice - Changsheng Li; Peng Wang; Guangliang Wu; Yanning Wang; Qin Cheng; Yicong Cai; Dahu Zhou; Caijing Li; Xiangyu Zhang; Jingai Tan; Cuijuan Li; Haohua He; et al. (Journal of Plant Growth Regulation, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

Mapping Domain- and Age-Specific Functional Brain Activity for Children’s Cognitive and Affective Development - Lei Hao; Lei Li; Menglu Chen; Jiahua Xu; Min Jiang; Yanpei Wang; Linhua Jiang; Xu Chen; Jiang Qiu; Shuping Tan; Jia-Hong Gao; Yong He; et al. (Neuroscience Bulletin, 2021)

Differential Physiological Responses of Small Thalassiosira pseudonana and Large Thalassiosira punctigera to the Shifted-High Light and Nitrogen - Zhen Qin; Xiaomin Xia; Guangming Mai; Yehui Tan; Gang Li (Journal of Marine Science and Engineering, 2021)
With global warming, the intensity and frequency of extreme episodic weather events such as typhoons are rising in tropical and subtropical regions, disturbing the water column and shifting phytoplankton therein from deep to surface layers, and exposing them to high light as well as nutrients. To explore how phytoplankton respond to such environmental changes, we tracked the growth, cell compositions and physiology of small Thalassiosira pseudonana and large Thalassiosira punctigera from simulated ambient to upward-shifted light and nitrogen (N) conditions. Shifting to high levels of light caused a limited effect on the growth of small T. pseudonana, but reduced that of large T. punctigera by 36%, with supplemental N alleviating the light-caused growth reduction. The upward-shifted light reduced the cellular pigments contents in small T. pseudonana, but not in large T. punctigera. The upward-shifted light reduced the photosynthetic capability (FV/FM) of both species, as well as the light utilization efficiency (α) and maximal relative electron transport rate (rETRmax), but it enhanced their dark reparations. Moreover, the upward-shifted light did not affect the superoxide dismutase (SOD) activity of small T. pseudonana, but it did enhance that of large T. punctigera. In addition, the supplemental N showed a limited effect on cellular pigments and the dark respiration of T. pseudonana, but it reduced that of T. punctigera. Our results showed that the growth responses of Thalassiosira to upward-shifted light and nitrogen vary with species and possibly with cell size, indicating that the field species composition might change after the occurrence of extreme weather events.

Regional Changes of Iris Stiffness in the Rabbits Suffered from Chronic High Intraocular Pressure - Tan Li; Xiao Qin; Haixia Zhang; Lin Li; Zhicheng Liu (Journal of Medical and Biological Engineering, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Insights into the Role of Magnesium Ions in Affecting Osteogenic Differentiation of Mesenchymal Stem Cells - Tiantian Qi; Jian Weng; Fei Yu; Weifei Zhang; Guoqing Li; Haotian Qin; Zhen Tan; Hui Zeng (Biological Trace Element Research, 2021)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Genetic analysis of germinating ability under alkaline and neutral salt stress by a high-density bin genetic map in rice - Xin Luo; Haodong Deng; Peng Wang; Xiangyu Zhang; Caijing Li; Cuijuan Li; Jingai Tan; Guangliang Wu; Yanning Wang; Qin Cheng; Haohua He; Jianmin Bian (Euphytica, 2020)

Optimization of an mRNA vaccine assisted with cyclodextrin-polyethyleneimine conjugates - Lu Tan; Tao Zheng; Man Li; Xiaofang Zhong; Yao Tang; Ming Qin; Xun Sun (Drug Delivery and Translational Research, 2020)

Optimizing the ratio of the spike to sample for isotope dilution analysis: a case study with selenium isotopes - Decan Tan; Wenpo Xu; Zuochen Zhu; Shehong Li; Guangliang Wu; Haibo Qin (Acta Geochimica, 2020)

Clinical and biochemical indexes from 2019-nCoV infected patients linked to viral loads and lung injury - Yingxia Liu; Yang Yang; Cong Zhang; Fengming Huang; Fuxiang Wang; Jing Yuan; Zhaoqin Wang; Jinxiu Li; Jianming Li; Cheng Feng; Zheng Zhang; Lifei Wang; et al. (Science China Life Sciences, 2020)

Rutin protects against pirarubicin-induced cardiotoxicity by adjusting microRNA-125b-1-3p-mediated JunD signaling pathway - Qi Li; Meng Qin; Tengteng Li; Zehui Gu; Qi Tan; Peng Huang; Liqun Ren (Molecular and Cellular Biochemistry, 2020)

Association of degree of loss aversion and grey matter volume in superior frontal gyrus by voxel-based morphometry - Ce Li; Xue-Qin Wang; Can-Hong Wen; Hai-zhu Tan (Brain Imaging and Behavior, 2020)

Altered functional connectivity of the posterior cingulate cortex in type 2 diabetes with cognitive impairment - Xin Tan; Yi Liang; Hui Zeng; Chunhong Qin; Yifan Li; Jinquan Yang; Shijun Qiu (Brain Imaging and Behavior, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

SQSTM1/p62 is involved in docosahexaenoic acid–induced cellular autophagy in glioblastoma cell lines - Xuefeng Tan; Linqing Zou; Jianbing Qin; Donglin Xia; Youlang Zhou; Guohua Jin; Zhuang Jiang; Haoming Li (In Vitro Cellular & Developmental Biology - Animal, 2019)

Study on Optimization of Roadway Position in Pre-mining Upper Layered Concave–Convex Coal Body - Wei Sun; Zhongcheng Qin; Qinghai Li; Guangbo Chen; Tan Li (Geotechnical and Geological Engineering, 2019)

Genetic diversity and pathogenicity dynamics of Magnaporthe oryzae in the Wuling Mountain area of China - Xin Xu; Wu Yang; Ke Tian; Jie Zheng; Xinqiong Liu; Kai Li; Wei Lu; Yanping Tan; Yonghua Qin; Chuntai Wang (European Journal of Plant Pathology, 2019)

The impact of Bt maize expressing the Cry1Ac protein on non-target arthropods - Yongjie Xing; Zifang Qin; Mingyue Feng; Aomei Li; Liu Zhang; Yang Wang; Xuehui Dong; Yuxin Zhang; Shuqian Tan; Wangpeng Shi (Environmental Science and Pollution Research, 2019)

New automated method for extracting river information using optimized spectral threshold water index - Chaojun Li; Shijie Wang; Xiaoyong Bai; Qiu Tan; Yujie Yang; Qin Li; Luhua Wu; Jianyong Xiao; Qinghuan Qian; Fei Chen; Huiwen Li; Yue Cao; et al. (Arabian Journal of Geosciences, 2019)

Genome-wide association analysis of intra-specific QTL associated with the resistance for enteric septicemia of catfish - Huitong Shi; Tao Zhou; Xiaozhu Wang; Yujia Yang; Chenglong Wu; Shikai Liu; Lisui Bao; Ning Li; Zihao Yuan; Yulin Jin; Suxu Tan; Wenwen Wang; et al. (Molecular Genetics and Genomics, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Comparison of diploid and triploid Carassius auratus provides insights into adaptation to environmental change - Li Ren; Xin Gao; Conghui Yang; Hui Tan; Jialin Cui; Shi Wang; Wuhui Li; Chun Zhang; Min Tao; Qinbo Qin; Shaojun Liu (Science China Life Sciences, 2018)

NLRP3 deficiency accelerates pressure overload-induced cardiac remodeling via increased TLR4 expression - Fangfang Li; Hao Zhang; Lu Yang; Hui Yong; Qingqing Qin; Mengtong Tan; Luhong Xu; Kai Liang; Jing Zong; Wenhao Qian (Journal of Molecular Medicine, 2018)

Using Illumina-Based Sequence Analysis to Guide Probiotic Candidate Selection and Isolation - Wenfeng Wang; Yi Li; Wangsen Qin; Changyi Sun; Hongming Tan; Lixiang Cao (Probiotics and Antimicrobial Proteins, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Dissecting the genetic basis of heavy panicle hybrid rice uncovered Gn1a and GS3 as key genes - Shiguang Wang; Bingtian Ma; Qiang Gao; Guojing Jiang; Lei Zhou; Bin Tu; Peng Qin; Xueqin Tan; Peixiong Liu; Yunhai Kang; Yuping Wang; Weilan Chen; et al. (Theoretical and Applied Genetics, 2018)

Evaluation of the Relationship Between Height and Zinc, Copper, Iron, Calcium, and Magnesium Levels in Healthy Young Children in Beijing, China - Yan Yin; Yongjin Li; Qin Li; Ni Jia; Aihua Liu; Zangwen Tan; Qiong Wu; Zhaoyang Fan; Tao Li; Lijun Wang (Biological Trace Element Research, 2017)

Overexpression of sugarcane gene SoSnRK2.1 confers drought tolerance in transgenic tobacco - Thi-Thu Phan; Bo Sun; Jun-Qi Niu; Qin-Liang Tan; Jian Li; Li-Tao Yang; Yang-Rui Li (Plant Cell Reports, 2016)

Estimation of the PM2.5 effective hygroscopic parameter and water content based on particle chemical composition: Methodology and case study - YueChen Liu; ZhiJun Wu; TianYi Tan; YuJue Wang; YanHong Qin; Jing Zheng; MengRen Li; Min Hu (Science China Earth Sciences, 2016)

Tissue-specific expression, developmentally and spatially regulated alternative splicing, and protein subcellular localization of OsLpa1 in rice - Hai-ping Lu; Wei-qin Pang; Wen-xu Li; Yuan-yuan Tan; Qing Wang; Hai-jun Zhao; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

EDARV370A associated facial characteristics in Uyghur population revealing further pleiotropic effects - Qianqian Peng; Jinxi Li; Jingze Tan; Yajun Yang; Manfei Zhang; Sijie Wu; Yu Liu; Juan Zhang; Pengfei Qin; Yaqun Guan; Yi Jiao; Zhaoxia Zhang; et al. (Human Genetics, 2016)

Bacterial growth efficiency in a partly eutrophicated bay of South China Sea: Implication for anthropogenic impacts and potential hypoxia events - Xing-Yu Song; Hua-Xue Liu; Yu Zhong; Ye-Hui Tan; Geng Qin; Kai-Zhi Li; Ping-Ping Shen; Liang-Min Huang; You-Shao Wang (Ecotoxicology, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Characterization of a new endo-type polyM-specific alginate lyase from Pseudomonas sp. - Ben-Wei Zhu; Li-Shu-Xin Huang; Hai-Dong Tan; Yu-Qi Qin; Yu-Guang Du; Heng Yin (Biotechnology Letters, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Fluorometric Titration Assay of Affinity of Tight-Binding Nonfluorescent Inhibitor of Glutathione S-transferase - Bangtian Xu; Deng Tan; Xiaolan Yang; Xiaolei Hu; Yanling Xie; Jialin Qin; Chunyan Chen; Chenxiong He; Yuanli Li; Jun Pu; Fei Liao (Journal of Fluorescence, 2015)

Overexpression of MpGR-RBP1, a glycine-rich RNA-binding protein gene from Malus prunifolia (Willd.) Borkh., confers salt stress tolerance and protects against oxidative stress in Arabidopsis - Yanxiao Tan; Yuan Qin; Yali Li; Mingjun Li; Fengwang Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

LIM-homeobox gene Lhx8 promote the differentiation of hippocampal newborn neurons into cholinergic neurons in vitro - Peipei Zhu; Haoming Li; Guohua Jin; Meiling Tian; Xuefeng Tan; Jinhong Shi; Linqing Zou; Jianbing Qin (In Vitro Cellular & Developmental Biology - Animal, 2013)

Lhx8 promote differentiation of hippocampal neural stem/progenitor cells into cholinergic neurons in vitro - Jinhong Shi; Haoming Li; Guohua Jin; Peipei Zhu; Meiling Tian; Jianbing Qin; Xuefeng Tan; Shuqing Zhao; Fuyu Wang; Yurong Hua; Yong Xiao (In Vitro Cellular & Developmental Biology - Animal, 2012)

Characterization and identification of Sox2+ radial glia cells derived from rat embryonic cerebral cortex - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Jinhong Shi; Weiwei Yang; Xuefeng Tan; Xinhua Zhang; Linqing Zou (Histochemistry and Cell Biology, 2011)

Generation and identification of rat fetal cerebral radial glia-like cells in vitro - Haoming Li; Guohua Jin; Jianbing Qin; Meiling Tian; Xuefeng Tan; Xinhua Zhang; Weiwei Yang; Jinhong Shi; Linqing Zou (In Vitro Cellular & Developmental Biology - Animal, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Overexpression of Trpp5 contributes to cell proliferation and apoptosis probably through involving calcium homeostasis - Yan Xiao; Xiaoyan Lv; Ge Cao; Guohui Bian; Jingjing Duan; Jianzhong Ai; Huan Sun; Qingwei Li; Qiutan Yang; Tielin Chen; Danhua Zhao; Ruizhi Tan; et al. (Molecular and Cellular Biochemistry, 2010)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Simple sequence repeat analyses of interspecific hybrids and MAALs of Oryza officinalis and Oryza sativa - Gang Li; Wei Hu; Rui Qin; Huajun Jin; Guangxuan Tan; Lili Zhu; Guangcun He (Genetica, 2008)